Mechanical Response and Elastocaloric Performance of Ni-Ti Shape Memory Alloy Sheets Under Varying Strain Rates - Gianmarco Bizzarri; Girolamo Costanza; Ilaria Porroni; Maria Elisa Tata (Compounds, 2025)
The optimization of elastocaloric cooling systems based on Shape Memory Alloys (SMAs) faces significant challenges in practical implementation. Despite promising thermomechanical properties, the development of efficient and compact cooling devices is hindered by incomplete understanding of strain rate effects on transformation behavior and energy conversion efficiency. While previous research has broadly characterized general SMAs’ thermomechanical behavior, the specific relationship between strain rate and elastocaloric performance in Ni-Ti sheets requires systematic investigation to overcome these barriers. This study investigates the strain rate dependence of Ni-Ti sheets’ properties through systematic mechanical characterization across strain rates ranging from <semantics>2.56×10−4<mspace width="3.33333pt"></mspace>s−1</semantics> to <semantics>6.15×10−3<mspace width="3.33333pt"></mspace>s−1</semantics>. Commercial Ni-Ti sheets underwent Shape Setting heat treatment and were characterized at eight different deformation levels using a universal testing machine equipped with a 50 kN load cell. Each deformation level was investigated through tests performed at four different crosshead speeds (1–24 mm/min), while monitoring stress-strain behavior and energy parameters. Results suggest distinct rate-dependent patterns in transformation stresses and energy dissipation characteristics across different strain rates. The analysis indicates that mechanical response and transformation behavior vary significantly between lower and higher strain rates, with implications for practical cooling applications. These findings aim to establish guidelines for optimizing elastocaloric performance by identifying suitable operating conditions for specific application requirements, considering factors such as energy conversion efficiency and cycling frequency.